Role of nucleus accumbens dopamine 2 receptors in motivating cocaine use in male and female rats prior to and following the development of an addiction-like phenotype - Towers, Eleanor Blair; Williams, Ivy L.; Qillawala, Emaan I.; Lynch, Wendy J. (Frontiers in Pharmacology, 2023)
A hallmark of cocaine use disorder (CUD) is dysfunction of dopamine signaling in the mesolimbic pathway, including impaired dopamine 2 (D2) receptor signaling. One of the most replicated findings in human imagining studies is decreased striatal D2 receptor binding in individuals with a substance use disorder relative to healthy controls; however, the vast majority of the data is from males, and findings in smokers suggest this molecular shift may not translate to females. The goal of this study was to determine whether there are sex differences in the role of D2 receptors in motivating cocaine use prior to and following the development of an addiction-like phenotype (defined by an enhanced motivation for cocaine relative to the shortaccess, ShA, group). Here, male and female rats were given ShA (20 infusions/day, 3 days) or extended-access (ExA; 24h/day, 96 infusions/day, 10 days) to cocaine self-administration and then following 14 days of withdrawal, were tested under a progressive-ratio schedule to assess motivation for cocaine use. Once a stable level of motivation was established, the effect of NAcinfusions of the D2 receptor antagonist eticlopride (0-3.0 µg/side) were examined. We found that in males, eticlopride was less effective at decreasing motivation for cocaine following ExA versus ShA self-administration, particularly at low eticlopride doses. In contrast, in females, there were no differences in the effectiveness of eticlopride between ExA and ShA. These findings indicate that males, but not females, become less sensitive to NAc-D2 receptor antagonism with the development of an addiction-like phenotype.